2019
DOI: 10.1016/j.electacta.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Capillary gap flow cell as capillary-end electrochemical detector in flow-based analysis

Abstract: Capillary gap flow cell as capillary-end electrochemical detector in flow-based analysis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…with the lowest reported for EC detection in flow-based analytical systems. The calculated LODs are about 2-times lower than the lowest reported LODs in our previous work [12] for 2,3-DHBA, and pyrocatechol as illustrated in Table 1. In this study, we observed 95 to 180-times improvement of current at 800 mV while comparing the voltammograms of solutes (ascorbic acid, 2,3-DHBA, and pyrocatechol, see SI Error!…”
Section: Mcontrasting
confidence: 59%
See 4 more Smart Citations
“…with the lowest reported for EC detection in flow-based analytical systems. The calculated LODs are about 2-times lower than the lowest reported LODs in our previous work [12] for 2,3-DHBA, and pyrocatechol as illustrated in Table 1. In this study, we observed 95 to 180-times improvement of current at 800 mV while comparing the voltammograms of solutes (ascorbic acid, 2,3-DHBA, and pyrocatechol, see SI Error!…”
Section: Mcontrasting
confidence: 59%
“…3-times) of the baseline noise and enhanced peak efficiency ca. 4-8% compared to reported EC detection in flow-based analytical systems [12] for all solutes, namely ascorbic acid, 2,3-dihydroxybenzoic acid and pyrocatechol.…”
Section: Mmentioning
confidence: 81%
See 3 more Smart Citations